Proinflammatory cytokine-induced tight junction remodeling through dynamic self-assembly of claudins - Capaldo, Christopher T. (The American Society for Cell Biology, 2014)
Tight junctions (TJs) are dynamic, multiprotein intercellular adhesive contacts that provide a vital barrier function in epithelial tissues. TJs are remodeled during physiological development and pathological mucosal inflammation, and differential expression of the claudin family of TJ proteins determines epithelial barrier properties. However, the molecular mechanisms involved in TJ remodeling are incompletely understood. Using acGFP-claudin 4 as a biosensor of TJ remodeling, we observed increased claudin 4 fluorescence recovery after photobleaching (FRAP) dynamics in response to inflammatory cytokines. Interferon γ and tumor necrosis factor α increased the proportion of mobile claudin 4 in the TJ. Up-regulation of claudin 4 protein rescued these mobility defects and cytokine-induced barrier compromise. Furthermore, claudins 2 and 4 have reciprocal effects on epithelial barrier function, exhibit differential FRAP dynamics, and compete for residency within the TJ. These findings establish a model of TJs as self-assembling systems that undergo remodeling in response to proinflammatory cytokines through a mechanism of heterotypic claudin-binding incompatibility.